A new species of sesarmid crab of the genus Chiromantes (Crustacea: Decapoda: Brachyura) from the Ogasawara Islands, Japan - Komai, Tomoyuki; Ng, Peter K.l. (Zootaxa, 2013)
A new species of sesarmid crab, Chiromantes magnus, is described from the Ogasawara (Bonin) Is., Japan. The new spe-cies was previously confused with C. dehaani (H. Milne Edwards, 1853). The different carapace shape, proportionally longer ambulatory legs, large adult size and the distinct live coloration distinguish the new species from its two closest congeners, C. dehaani and C. neglectus (De Man, 1887). Available information indicates that C. magnus n. sp. is endemic to the Ogasawara Is.; there is no evidence of the occurrence of the true C. dehaani in the Ogasawara Is.